2010
DOI: 10.1186/1471-2156-11-95
|View full text |Cite
|
Sign up to set email alerts
|

Genetic predisposition for femoral neck stress fractures in military conscripts

Abstract: BackgroundStress fractures are a significant problem among athletes and soldiers and may result in devastating complications or even permanent handicap. Genetic factors may increase the risk, but no major susceptibility genes have been identified. The purpose of this study was to search for possible genetic factors predisposing military conscripts to femoral neck stress fractures.ResultsEight genes involved in bone metabolism or pathology (COL1A1, COL1A2, OPG, ESR1, VDR, CTR, LRP5, IL-6) were examined in 72 mi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
36
0
1

Year Published

2013
2013
2022
2022

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 41 publications
(37 citation statements)
references
References 48 publications
0
36
0
1
Order By: Relevance
“…Associations were shown for SNPs and haplotype blocks within the vitamin D receptor (13) and an androgen receptor repeat sequence (14). However, other studies have shown no association for the same SNPs in similar military populations (15).…”
Section: Introductionmentioning
confidence: 92%
“…Associations were shown for SNPs and haplotype blocks within the vitamin D receptor (13) and an androgen receptor repeat sequence (14). However, other studies have shown no association for the same SNPs in similar military populations (15).…”
Section: Introductionmentioning
confidence: 92%
“…It is possible that the observed rare variants may contribute to fractures in association with other unfavorable environmental and genetic factors. Previous studies found that the LRP5 haplotype (E644E, V667M, V1119V, and A1330V), in combination with the vitamin D receptor haplotype, was associated with stress fractures (Korvala et al, 2010).…”
Section: Discussionmentioning
confidence: 99%
“…The HWE test was performed on genotype distribution of the controls, and all of them were in agreement with HWE, except Saarinen et al (2010). There were 3 studies conducted on Asian populations (Mizuguchi et al, 2004;Liu et al, 2010;Xuan et al, 2014) and 4 studies on Caucasian populations (Ferrari et al, 2005;Hartikka et al, 2005;Korvala et al, 2010;Saarinen et al, 2010). Table 2 lists the main results of the pooled analysis and Figure 2 shows the association of the LRP5 Ala1330Val polymorphism with fracture risk in the form of forest plots.…”
Section: Study Characteristicsmentioning
confidence: 99%
See 1 more Smart Citation
“…Genetic factors may play a role in the development of stress fractures in individuals subjected to heavy exercise and mechanical loading [5]. Also stress fracture of the femoral neck in active adults is known to be related with coxa vara [1].…”
Section: Discussionmentioning
confidence: 99%